Por uma reformulação do empirismo construtivo a partir de uma reavaliação do conceito de observabilidade - Alessio Gava (2015)
The concept of observability is of key importance for a consistent defense of Constructive Empiricism. This anti-realist position, originally presented in 1980 by Bas van Fraassen in his book The Scientific Image, crucially depends on the observable/ unobservable dichotomy. Nevertheless, the question of what it means to observe has been faced in an unsatisfactory and inadequate manner by van Fraassen and this represents an important lacuna in his philosophical position. The aim of this work is to propose a characterization of the act of observation able to give the necessary support to the ‘rough guide’ of ‘observable’ that can be found in the aforementioned book. Countering van Fraassen’s own statements, that observability is not a matter for philosophy, but for scientific inquiry only, we maintain that any attempt to deal with this subject by the philosophers is legitimate. We will show that van Fraassen ended up doing a philosophical analysis of observation himself, albeit in a fragmentary way. We believe that this question should be dealt with methodically, though, ‘following the rules’ of a ‘proper’ philosophical analysis, as we attempted to do in this work. We will propose a way of conceiving the act of observation, different from van Fraassen’s one, that can help not only to ground the distinction between observable and unobservable, upon which Constructive Empiricism rests, but to get this anti-realist position closer to scientific practice as well, which is one of its desiderata. Without neglecting the philosophical dimension of the issue, though. However, this proposal does not represent an ad hoc ‘solution’ for Constructive Empiricism, but a characterization aspiring to have a universal reach.